Identification of biofilms in post‐tympanostomy tube otorrhea. (4th January 2016) - Idicula, Winslo K.; Jurcisek, Joseph A.; Cass, Nathan D.; Ali, Syed; Goodman, Steven D.; Elmaraghy, Charles A.; Jatana, Kris R.; Bakaletz, Lauren O.
Abstract : Objectives/Hypothesis: Otitis media is a common problem in the pediatric population. Despite antibiotic therapy, post‐tympanostomy otorrhea can be difficult to treat. Biofilms have been shown to play a role in chronic and recurrent otitis media and are implicated in otorrhea. This study investigated both the microbial composition and the presence of biofilm fragments rich in extracellular DNA (eDNA) and the bacterial DNA‐binding protein, integration host factor (IHF), in post‐tympanostomy tube otorrhea. Study Design: Clinical samples. Methods: Institutional review board approval was obtained, and samples were recovered from pediatric patients with tympanostomy tubes and persistent otorrhea for both microbial culture and biofilm analysis. For biofilm assessment, frozen samples were sectioned and then labeled using a rabbit anti‐IHF, which was detected with goat anti‐rabbit IgG conjugated to AlexaFluor 594. Samples were then counterstained with 4', 6‐diamidino‐2‐phenylindole (DAPI) to detect DNA, and images were captured by inverted light microscopy. Results: Of 15 pediatric otorrhea samples analyzed, nine (60%) contained solids that were positive for labeling of IHF in association with a lattice of eDNA, and 75% yielded positive bacterial cultures. Bacterial culture results included H. influenzae, Methicillin‐resistant Staphylococcus aureus, S. pneumoniae, M. catarrhalis, and P. aeruginosa . Conclusion: Positive labeling of otorrhea solids for eDNA and IHF, in combination with microbiological culture results, indicated that biofilms likely played a key role in chronic otorrhea. Moreover, as a known critical structural component of biofilms, these findings suggest that DNABII proteins in association with eDNA may serve as an important therapeutic target in post‐tympanostomy tube otorrhea. Level of Evidence: NA. Laryngoscope, 126:1946–1951, 2016